Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.14712/18059694.2018.102
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Serum Magnesium with Dyslipidemia in Maintenance Hemodialysis Patients

Abstract: One of the factors involved in accelerated atherosclerosis in hemodialysis patients is dyslipidemia. In this study we considered factors involved in intensification of dyslipidemia in hemodialysis patients.This study was done on 36 maintenance hemodialysis patients. Serum lipoprotein (a), Triglyceride, Cholesterol, HDL-C,LDL-C and also serum Intact parathormone( iPTH), Calcium, Phosphorus, Magnesium were measured. In statistical analysis there was not any correlation between serum lipids and iPTH. There was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 11 publications
(14 reference statements)
5
25
0
Order By: Relevance
“…HDL-cholesterol level showed a significant decrease in ketotic buffalo in comparison to the subclinical and control groups. These results coincide with those of Nasri and Baradaran (2004) and Turk et al (2008). These results may be attributed to moderate liver steatosis, which causes reduction in cholesterol level.…”
Section: Discussionsupporting
confidence: 87%
“…HDL-cholesterol level showed a significant decrease in ketotic buffalo in comparison to the subclinical and control groups. These results coincide with those of Nasri and Baradaran (2004) and Turk et al (2008). These results may be attributed to moderate liver steatosis, which causes reduction in cholesterol level.…”
Section: Discussionsupporting
confidence: 87%
“…We also observed an association of lowered magnesium concentration with atherogenic dyslipidemia, an important adverse risk factor for the development of cardiovascular disease. This is in contrast to the findings of Baradaran et al [30] who found no existent correlation between lipid profile and serum magnesium, but in concordance with Ansari et al [31], who identified an association of triglycerides alone with serum magnesium and animal studies and other human studies which show a positive correlation and amelioration of dyslipidemia on supplementation of magnesium [32][33][34].…”
Section: Discussionsupporting
confidence: 80%
“…The effect may be mediated through anti‐inflammatory mechanisms because leptin has structural and functional similarities with members of the cytokine family (Pecoits‐Filho et al. , 2003) and enhances cytokine production by macrophages and monocytes (Nasri & Baradaran, 2005). This indicates that fish oil may be an effective therapy for improvement of appetite in dialysis patients and warrants future research.…”
Section: Discussionmentioning
confidence: 99%